Perancangan Aplikasi Pelacak Mood Dengan Scan Wajah - Sofyan Mufti Prasetiyo; Anzal Fadly Hadi Pratama; Wike Rahayu; Yusri Nuraeni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Mood is a psychological condition that involves emotion without any existence emotional object. Although it exists as an abstract psychological variable, the contribution of emotion towards human behavior is massively important. Many studies related to emotion and human behavior have shown that individual mood (positive or negative) will have different behavioral consequences. In order to understand mood comprehensively in Indonesian context, we need a valid and reliable measurement scale. The purpose of this study is to investigate the validity and reliability of Four Dimensions Mood Scale (FDMS) as a psychological tool to classify mood condition into four primary dimensions, positive energy; tiredness; negative activation and relaxation. Finally, author hopes that this study will give an empirical contribution so that FDMS is able to use in Indonesian context.